Co‐localization of insect olfactory sensory cells improves the discrimination of closely separated odour sources. (3rd March 2014) - Binyameen, Muhammad; Jankuvová, Júlia; Blaženec, Miroslav; Jakuš, Rastislav; Song, Liwen; Schlyter, Fredrik; Andersson, Martin N.; Fox, Charles
Summary The sense of smell is crucial for fitness of most animals, enabling them to find mates, food and egg laying sites and to stay away from danger. Hence, odour molecules are detected by sensitive and specific olfactory sensory neurons (OSNs). In insects, the OSNs are stereotypically grouped into olfactory sensilla located mainly on the antennae. The functional significance of this co‐localization principle is poorly understood, but it has been hypothesized that it allows for coincidence detection of odour filaments, improving discrimination of closely separated odour sources. Using an insect in its natural environment, we conducted the first experimental test of the hypothesis. We manipulated the distance between odour sources of an attractive pheromone and either of two host‐derived attraction antagonists (1, 8‐cineole and verbenone) and investigated the effect on trap catches of the bark beetle, Ips typographus (Coleoptera). 1, 8‐Cineole is detected by an OSN co‐localized with an OSN for one of the pheromone components, while verbenone is detected by OSNs in other sensilla, not co‐localized with pheromone OSNs. Consistent with the hypothesis, trap catch increased with distance between odour sources more for 1, 8‐cineole than for verbenone. The strongest effect was found among the males, that is the sex that first locates and attacks the host tree. Our data from the beetle provide, for the first time, direct experimental support for the hypothesis that co‐localization of OSNs in sensilla improves the discrimination of closely separated odour sources. Thus, selection for improved odour source discrimination could well be one of the factors explaining the strict co‐localization of OSNs that is seen across the Insecta class.